Malnutrition among first year school children in Iraq - Al-shammary, Nadher; Al-Diwan, Jawad K.; Al-Ani, Nafi (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Iraqi people have endured an excess burden of morbidity’ and mortality during the last two decades due to wars and sanctions. This report M’as carried out to assess the nutritional status of first year primary school children. Methods: A total of3881 school children in Balad district in Salahadin govemorate was included in the study. Age, height and weight were recorded. Malnutrition was regarded as value of less than 2 SD of the reference value. Results: Among the total sample, 16.5%, 20.06% and 15.3% were underweight, stunted and wasted, respectively. No significant difference was detected in malnutrition rates between both sexes. Conclusion: High rates of malnutrition were detected among school children.